Pengaruh Konten Youtube Ria Ricis Terhadap Agresi Verbal Netizen - Aulia Rahma; Delliana, Santi (Universitas Islam Balitar, 2022)
More and more content creators have begun creating YouTube videos in Indonesia. One of Indonesia's famous YouTubers is named Ria Ricis. The popularity of Ria Ricis on YouTube has brought many subscribers to her. One of the Ria Ricis videos that this research focuses on was a video entitled